2012
DOI: 10.1007/s12094-012-0849-4
|View full text |Cite
|
Sign up to set email alerts
|

Fifty percent patients avoid whole brain radiotherapy: stereotactic radiotherapy for multiple brain metastases. A retrospective analysis of a single center

Abstract: Our data suggest that use of SRT as the initial treatment while reserving WBRT as the salvage therapy in case of distant intracranial recurrence made about 50 % of the patients avoid WBRT throughout the course of their lives and may be another optional treatment modality for multiple brain metastases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 28 publications
1
9
0
Order By: Relevance
“…Our findings add to the growing body of evidence supporting intensive local and multifocal treatment for brain metastases 12,30,[32][33][34] with sparing of the surrounding white matter fibers, vessels, and myelin in an effort to preserve NCF. 35 Neurocognitive testing provides a quantitative tool for monitoring the effects of therapy and developing tailored therapies to enhance functional well being.…”
Section: Discussionsupporting
confidence: 63%
“…Our findings add to the growing body of evidence supporting intensive local and multifocal treatment for brain metastases 12,30,[32][33][34] with sparing of the surrounding white matter fibers, vessels, and myelin in an effort to preserve NCF. 35 Neurocognitive testing provides a quantitative tool for monitoring the effects of therapy and developing tailored therapies to enhance functional well being.…”
Section: Discussionsupporting
confidence: 63%
“…Although, neurocognitive outcomes [46] and quality of life [47] were worse in the early WBRT group. Therefore, some authors suggest that WBRT after SR or SRS could be avoided in some cases, especially in patients with subtypes of MBC who live longer than the the more aggressive triple negative subtypes [48]. …”
Section: Local Treatmentmentioning
confidence: 99%
“…A randomized trial of osimertinib with or without SRS for EGFR-mutated NSCLC with BMs from the Trans-Tasman Radiation Oncology Group to compare the iPFS at 12 months is ongoing (NCT03497767). We had previously explored the effectiveness of upfront SRS and deferred WBRT in BM patients with focus larger than 3 cm (23). The results showed that the use of SRS as the initial treatment while reserving WBRT as the salvage therapy in case of distant intracranial recurrence made about 50% of the patients avoid WBRT throughout their lives.…”
Section: Discussionmentioning
confidence: 99%
“…We had previously explored the effectiveness of upfront SRS and deferred WBRT in BM patients with focus larger than 3 cm ( 23 ). The results showed that the use of SRS as the initial treatment while reserving WBRT as the salvage therapy in case of distant intracranial recurrence made about 50% of the patients avoid WBRT throughout their lives.…”
Section: Discussionmentioning
confidence: 99%